Novel Levilactobacillus brevis-based formulation for controlling cell proliferation, cell migration and gut dysbiosis. (15th January 2022) - Mahanta, Sachin; Prusty, Monica; Sivakumar, P.S.; Mishra, Deepak; Sahu, Ram Prasad; Goswami, Chandan; Chawla, Saurabh; Goswami, Luna; Elangovan, Selvakumar; Panda, Sandeep Kumar
Abstract: The objective of the study was to formulate a novel Levilactobacillus brevis enriched nutraceutical and to study its functional property in vitro in cancer cell lines and in vivo in Salmonella enterica serovar Typhimurium infected mouse model. The formulation was prepared through the fermentation of carrot and beetroot extracts using L. brevis MTCC 4460 and optimized by response surface methodology and artificial neural networking. The optimized formulation (3.23 mg/ml lactic acid) could be obtained through 48 h fermentation with 2% of bacterial inoculum, 0.67% additional sugar and 30.11% of beetroot extract. The L. brevis MTCC 4460 content in the optimized product was 4 × 10 9 CFU/ml. GC-MS study indicated the generation of some novel flavouring and bioactive compounds such as γ-decalactone, and 1, 2:5, 6-dianhydrogalactitol during the fermentation. In vitro study with HCT116 and MDA-MB-231 cancer cell lines elucidated better antiproliferative and antimigratory effect of the optimized formulation. In vivo studies showed that the L. brevis MTCC 4460 could colonize in the colon of the mouse fed with the optimized product. In addition, the formulation effectively prevented Salmonella -induced colitis in the mouse model. Based on the aforesaid findings, the optimized formulation can be recommended as a potential dietary supplement for a healthy lifestyle. Highlights: Levilactobacillus brevis based formula was prepared with carrot and beetroot extracts. The formulation exhibited a protective role in cell proliferation and migration. The nutraceutical inhibited the Salmonella infection in the colon and spleen. The formulation has the potential for commercialization as a functional food.